2001
DOI: 10.1007/s005350170033
|View full text |Cite
|
Sign up to set email alerts
|

Association of the interleukin-1 * genetic polymorphism and gastric cancer risk in Japanese

Abstract: The IL-1 beta-511 genetic polymorphism was not associated with gastric cancer in a multistep carcinogenesis model. However, in view of the results for the IM or CAG without H. pylori group, the presence of the C allele may also indicate a risk of mucosal atrophy of the stomach in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
115
4
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 15 publications
14
115
4
1
Order By: Relevance
“…32 In order to assess the association with gastric cancer, we first analyzed the inflammatory polymorphisms using univariate statistics of each diplotype in the same fashion as others. [9][10][11][12]32,33 Although a tendency of association between gastric carcinoma and IL1RN heterozygote was observed, the other cytokine genotypes were not significantly associated with the disease. Since the polymorphic allele of IL1RN is rare in our population, it could be difficult to demonstrate a role for the inflammatory homozygotes, although the gastric carcinoma risk for those individuals could be even higher.…”
Section: Discussionmentioning
confidence: 85%
“…32 In order to assess the association with gastric cancer, we first analyzed the inflammatory polymorphisms using univariate statistics of each diplotype in the same fashion as others. [9][10][11][12]32,33 Although a tendency of association between gastric carcinoma and IL1RN heterozygote was observed, the other cytokine genotypes were not significantly associated with the disease. Since the polymorphic allele of IL1RN is rare in our population, it could be difficult to demonstrate a role for the inflammatory homozygotes, although the gastric carcinoma risk for those individuals could be even higher.…”
Section: Discussionmentioning
confidence: 85%
“…The C allele was designated if 2 bands of 88 and 67 bp were obtained and the T allele was designated if a single band of 155 bp was obtained. 22 The PCR products for tandem repeat polymorphisms of IL-1RN were used directly for electrophoresis. The IL-1RN gene has a pentaallelic 86 bp tandem repeat (VNTR) at intron 2, 26 and the alleles were coded conventionally as follows: allele 1, 4 repeats; allele 2, 2 repeats; allele 3, 5 repeats; allele 4, 3 repeats; and allele 5, 6 repeats (Table II).…”
Section: Genotyping Of Il-1a Il-1b and Il-1rnmentioning
confidence: 99%
“…However, ethnicity might greatly affect genotype status, and 2 recent studies revealed no difference in IL-1B-511 genotypes between GC and controls in Japanese and Taiwanese populations. 22,23 Even within Asia, the IL-1B polymorphisms differ between northern (Japanese and Chinese) and southern (Thai and Vietnamese) populations. In subjects with severe gastric mucosal atrophy, the IL-1B-511C/C polymorphism was dominant in the Japanese population and the IL-1B-511T/T ϩ T/C polymorphism was dominant in the Chinese population; however, no differences in C-and T-allele frequencies were found in the Thai and Vietnamese populations.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 It is becoming evident, however, that even in these Asian populations, one has to consider the background incidence of the cancer in question. Thus, Zeng et al 22 reported recently that IL-1B-511T/T genotype was a significant risk factor for gastric cancer in low incidence areas of China but that the effect of this genotype was less obvious in areas of high incidence.…”
Section: Il-1b-31(c/t) Tnf-a-308mentioning
confidence: 99%